Copper Nanoparticles in Liquid by a Non-capacitive Wire Explosion Technique - Andrea P. Reverberi; Virginia Bazzurro; Anna Maria Cardinale; Marco Vocciante; Omar Soda; Bruno Fabiano (Chemical Engineering Transactions)
An experimental study for copper nanoparticles (NPs) synthesis in aqueous phase, relying upon a physical top-down technique, is proposed. It differs from the well-known wire-explosion protocol, in that two wire-shaped conductors, made of metal precursors of different sections, undergo a short circuit at low voltage where a high current density leads to an instantaneous disaggregation of preferentially one of the two electrodes immersed in a liquid phase, without establishing a stable arc-discharge regime. The as-obtained NPs have been characterized in size by dynamic light scattering (DLS) and in morphology by transmission electron microscopy (TEM). Two non-ionic polymeric capping agents having the same monomeric structure, but differing from one another in molecular weight, have been dissolved in the liquid holdup and the average diameter of the as-obtained Cu NPs is 63 and 72 nm. The present work, thanks to a relatively easy experimental setup and to the mitigation of risk conditions usually related to the use of high voltages, may represent a promising technique in alternative to other physical top-down methods for a sustainable and cost-effective metal NPs synthesis.